Childhood food allergy and food allergen sensitisation are associated with adult airways disease: A birth cohort study. Issue 8 (21st July 2021) - Fong, Wei Chern Gavin; Chan, Adrian; Zhang, Hongmei; Holloway, John W.; Roberts, Graham; Kurukulaaratchy, Ramesh; Arshad, Syed Hasan
Abstract: Background: Childhood food allergy (FA) and food allergen sensitization (FAS) are associated with allergic airway disease(s) [AAD] (asthma and rhinitis) in childhood. However, the associations between childhood FA/FAS and AAD in adulthood are not well described. Methods: We investigated the longitudinal relationship between childhood FA/FAS to common food allergens and AAD at 18 and 26 years, in the Isle of Wight birth cohort. Study subjects ( N = 1456) were followed up at fixed time points from ages 1–26 years for FA/FAS status. AAD were evaluated from 4 years onwards. The associations between FA/FAS and AAD were assessed with univariate analyses and then multivariable logistic regression, adjusting for clinically relevant co‐variates. Results: Food allergy at 4 years was significantly associated with asthma at 18 years [adjusted odds ratio (aOR): 2.75, 95% CI: 1.53–4.92, p = .001] and 26 years (aOR: 2.62, 95% CI: 1.32–5.20, p = .006). Conversely, childhood FA was not associated with adulthood rhinitis whatsoever. While FAS at ages 4 and 10 were associated with both AAD, the associations between FAS and rhinitis were less robust relative to asthma. Conclusion: Childhood FA increased the odds of asthma during adulthood by nearly threefold. Additionally, childhood FAS was also associated with increased odds of asthma in adulthood. Conversely, FAS but not FA in childhood was associated with rhinitis in adulthood. We suggest that children with FA/FAS should be followed up to facilitate early detection and intervention of subsequent AAD, particularly asthma.